2007
DOI: 10.1055/s-2006-927183
|View full text |Cite
|
Sign up to set email alerts
|

Visual Rating of T2’-Blood-Oxygen-Level-Dependent Magnetic Resonance Imaging in Acute Stroke Patients - a Pilot Study

Abstract: Hypo-intense lesions in BOLD imaging were visible and exceeded the lesion in diffusion-weighted imaging in most of the stroke patients. The encouraging results justify further testing of the hypothesis that BOLD lesions, when larger than DWI lesions, are associated with infarct growth from initial DWI to final infarct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…They have been used to describe the penumbra in acute stroke patients (Lee et al, 2003;Geisler et al, 2006;Fiehler et al, 2007). This approach is based on a metabolic concept.…”
Section: Introductionmentioning
confidence: 99%
“…They have been used to describe the penumbra in acute stroke patients (Lee et al, 2003;Geisler et al, 2006;Fiehler et al, 2007). This approach is based on a metabolic concept.…”
Section: Introductionmentioning
confidence: 99%
“…1 for an illustration). Furthermore, in a pilot report by Fiehler et al [17] involving the same dataset as Geisler et al [16], the interobserver agreement for correctly identifying the affected side was considered ‘fair’ only (ĸ = 0.239), and after unblinding the visibility of the T2’ hypo-intense lesion was considered ‘good’ in only 9 out of 20 patients by consensus, raising questions about the method’s reliability in the clinical setting – notwithstanding that some of the images presented are quite convincing. In a further report from the same group on 100 patients [18], the T2’-apparent diffusion coefficient mismatch had better specificity than the PWI-apparent diffusion coefficient mismatch for predicting infarct growth; however, there was high variability in T2’ lesions visibility and the interobserver reliability was moderate only (ĸ = 0.53).…”
Section: Discussionmentioning
confidence: 99%
“…In a subsequent study, Fiehler and coworkers 35 concluded that T2' may be sensitive to infarct growth, but that the T2' lesion can be difficult to assess visually.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Eleven experimental studies have used T2* with breathing challenge [25][26][27][28][29][30][31][32][33][34][35] (online-only Data Supplement Table III). During anoxic challenge, image intensity in T2*-weighted images significantly dropped in the core, penumbra, and healthy tissue, but these changes could not clearly differentiate these tissue types without the information from diffusion-weighted imaging.…”
Section: T2* With Breathing Challengementioning
confidence: 99%